Exploring the perception of pre-clinical and clinical educators on clinical reasoning: A qualitative study. - Siti Norashikin Mohd Tambeh; Farah Dayana Zahedi; Mohamad Nurman Yaman (PLoS ONE)
Introduction Educators have differing perception on the definition and conceptualization of clinical reasoning. Even though clinical reasoning is important in making a sound diagnosis and reducing diagnostic error, educators proved to be a barrier in teaching clinical reasoning due to the lack of awareness of their own reasoning process. Objectives This study was conducted to investigate the perception and understanding of pre-clinical and clinical educators on what clinical reasoning entails, their experience, and educational strategies in teaching clinical reasoning. Method A semi-structured interview was conducted with fifteen educators encompassing pre-clinical (basic science, laboratory-based) and clinical (surgical-based, medical-based, community-based and emergency medicine) educators. The transcribed interview data was then analysed thematically. Results Eight main themes were identified. Knowledge and experience were seen as important components in developing clinical reasoning. It was possible to teach clinical reasoning although there were some difficulties thus the need to have a train-the-trainer programme. Early introduction of clinical reasoning with its incorporation in various teaching and learning method; and the involvement of technological advances were also mentioned by the participants. However, pre-clinical educators did not perceive the importance of these technological advances. Role of educators; cognitive and non-cognitive attributes were also important in developing clinical reasoning. Conclusion The perception and understanding of pre-clinical and clinical educators on clinical reasoning did not really differ. They believed that clinical reasoning can be taught, and a train-the-trainer program may be of immeasurable benefit.